Work Related Traumatic Dental Injuries, and their Detrimental Effects on Dentition and Oral Health - Tomevska, Marija; Kawar, Nadia (European Journal of Applied Sciences, 2026)
Jobs that require physical labor for extended hours over a prolonged period, such as working in the construction industry, put workers at higher risk of experiencing occupational hazards. In addition to the intensity of the physical labor, these jobs may also expose workers to chemicals or harsh work environment such as working outdoors, exposure to weather and dust particles and high altitudes or underground. The effect on physical well-being has been studied and protective safety equipment such as helmets are mandated and enforced to protect against physical injury. However not many studies have investigated the effect on dentition and oral health. There is not much attention given to implementing protection against dental and oral trauma. Through clinical observation and review of literature review, construction workers are showing signs of chronic dental trauma resulting in advanced dental treatment needs. Work related traumatic dental injuries have resulted in specific pattern of fractured teeth, loss of tooth structure, dental infections, malocclusion, Temporomandibular joint dysfunction and edentulism. (1) Dental treatment of these conditions costly, requiring multiple dental visits and multispecialty collaboration often needing a full mouth rehabilitation to restore lost dental structure and altered facial dimensions. The purpose of this article is reviewing available literature using the various internet platforms such as PubMed and Google Scholars, to explore the different work conditions that can result in traumatic dental injuries, to highlight their detrimental effects on dentition and oral health and finally to propose implementing and a mandating protective appliance for workers.